Disseminated Histoplasmosis with Miliary Histoplasmosis, Neurohistoplasmosis, and Histoplasma capsulatum Bacteremia in Probable Neurosarcoidosis - Peter V. Bui (Case Reports in Medicine)
Introduction. Neurosarcoidosis, either isolated or as part of systemic sarcoidosis, is an uncommon entity and has diagnostic uncertainty. Treatment for neurosarcoidosis can increase the risk of infections, including fungal infections such as disseminated histoplasmosis. Neurosarcoidosis may further predispose patients to infections of the central nervous system. Case Presentation. A 54-year-old male with a history of probable neurosarcoidosis on methotrexate and infliximab presented with encephalopathy, hypoxia, and reported fevers. The patient was found to have disseminated histoplasmosis involving the lungs (miliary histoplasmosis), central nervous system (neurohistoplasmosis), and bloodstream. The Histoplasma capsulatum infection was treated with amphotericin and then voriconazole. Discussion. Patients with neurosarcoidosis are suspected to have blood-brain barrier dysfunction. Lumbar puncture should be considered as part of initial investigative studies for infection. Empiric antimicrobial therapy for a patient with neurosarcoidosis on immunosuppressive agents may need to include antifungal agents.